Ground state of the Fe(ii)-porphyrin model system corresponds to quintet: a DFT and DMRG-based tailored CC study. Issue 30 (27th July 2020) - Antalík, Andrej; Nachtigallová, Dana; Lo, Rabindranath; Matoušek, Mikuláš; Lang, Jakub; Legeza, Örs; Pittner, Jiří; Hobza, Pavel; Veis, Libor
Abstract : Fe(ii )-porphyrins play an important role in many reactions, due to their closely lying spin states. We present a thorough study of a Fe(ii )-porphyrin model system, in which we examine how the geometrical parameters influence its spin state ordering. Abstract : Fe(ii )-porphyrins play an important role in many reactions relevant to material science and biological processes, due to their closely lying spin states. Although the prevalent opinion is that these systems posses the triplet ground state, the recent experiment on Fe(ii )-phthalocyanine under conditions matching those of an isolated molecule points toward the quintet ground state. We present a thorough DFT and DMRG-based tailored CC study of Fe(ii )-porphyrin model, in which we address all previously discussed correlation effects. We examine the importance of geometrical parameters, the Fe–N distances in particular, and conclude that the system possesses the quintet ground state.